I mercanti lettori del Petrarca - Brambilla, Simona (Verbum – Analecta Neolatina, 2005)
The article is divided into two parts. The first part analyses how, between the 14th and the 16th century, the Italian merchants read the works of Petrarch, paying attention to material aspects, such as ownership, support, mercantesca hand, language and circulation; the study is based on the available catalogues of manuscripts by Petrarch. The second part studies the circulation of Petrarch's works among a small group of readers who lived in Florence and Prato (late 14th and early 15th century): the merchant and politician Guido del Palagio, the merchant Francesco Datini, the notary Lapo Mazzei and two churchmen, Giovanni dalle Celle and Luigi Marsili. The paper is based on material already published as well as research in archives.